The role of the renin-angiotensin system (RAS) in salinity adaptation in Pacific white shrimp (Litopenaeus vannamei) - Farhadi, Ardavan; Liu, Yan; Xu, Chang; Wang, Xiaodan; Li, Erchao (Frontiers in Endocrinology, 2022)
The renin-angiotensin system (RAS) is a hormonal system that plays an important role in the regulation of blood pressure and cardiovascular homeostasis in mammals. In fishes, the RAS pathway participates in osmoregulation and salinity adaptation. However, the role of the RAS pathway in invertebrates, particularly in crustaceans, remains unknown. In this study, four key genes of the RAS pathway (LV-ACE, LV-APN, LV-AT1R, and LV-RR) were cloned, characterized, and their expression levels were detected in the eyestalk, hepatopancreas, and muscle of Litopenaeus vannamei during long-term and short-term low salinity stress. The results showed that LV-ACE, LV-APN, LV-AT1R, and LV-RR encode 666, 936, 175, and 323 amino acids, respectively. Low salinity stress downregulated the expression levels of LV-ACE, LV-APN, LV-AT1R, and LV-RR in L. vannamei, indicating that the RAS pathway was suppressed under low salinity. Moreover, these genes play important roles in the regulation of drinking rate, controlling urine output, blood glucose, and blood pressure, indicating that their downregulation probably affected the homeostasis of shrimps. These findings provide novel insights into the mechanism of salinity adaptation in L. vannamei.